Effects of lipopolysaccharides on TLR4 expression in INS-1 rat insulinoma cells - Ge, Q-M.; Du, S-C.; Bian, F.; Lin, N.; Su, Q. (Cellular and Molecular Biology, 2011)
The aim of the study was to obtain insight into the mechanism of sepsis-induced hyperglycemia, to explore the expression of toll-like receptor 4 (TLR4) on INS-1 cells, the effects of lipopolysaccharide (LPS) on TLR4 expression and cell viability. The expression of TLR4 on INS-1 was detected by both RT-PCR and Western blot assays. After being intervened by LPS of various concentrations (0.01, 0.1, 1, 5, 10mg/L) for a certain time, the effects of LPS on TLR4 expression and cell viability were detected by quantitative real-time reverse-transcriptase polymerase chain reaction, western blotting and CCK-8 assay. Then INS-1 cells were stimulated by LPS (0.1, 1mg/L) together with anti-TLR4 antibody, cell viability and TLR4 expression were detected again. TLR4 expressed in INS-1 cell line. Its expression was up-regulated by the stimulation of LPS higher than 0.1mg/L for 12h (P<0.05). However, there was a little down regulation of TLR4 between the LPS treated groups and controls with further LPS treatment for 24 and 48h (P>0.05). In certain concentrations(0.1ï½ž10mg/L), viability of INS-1 cells was inhibited by LPS in a dose dependent manner (P<0.05)ï¼ŽThese effects could be blocked by anti-TLR4 antibody partially. These results suggest that LPS may act directly on the pancreatic Î² cells via TLR4 on the Î²-cell membrane. LPS increased TLR4 expression in the early short period of time and caused injury to INS-1 cells after a certain time. It could be one of the mechanisms that hyperglycemia occurs in the early stage of sepsis.